2000
DOI: 10.1007/978-3-642-57273-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Quantum Similarity in QSAR and Drug Design

Abstract: Includes bibliographical references and index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
93
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 0 publications
1
93
0
Order By: Relevance
“…Over a series of five groups of benzoic acid derivatives, each containing seven to eight molecules, a correlation could be established with a regression coefficient over 96%. 174 Similar results were obtained by Carbó -Dorca et al 10 for yet another series of 12 benzoic acid derivatives. In all cases, the fragment self-similarity was calculated for a fragment F, containing the atoms a as…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Over a series of five groups of benzoic acid derivatives, each containing seven to eight molecules, a correlation could be established with a regression coefficient over 96%. 174 Similar results were obtained by Carbó -Dorca et al 10 for yet another series of 12 benzoic acid derivatives. In all cases, the fragment self-similarity was calculated for a fragment F, containing the atoms a as…”
supporting
confidence: 90%
“…53 However, it has been not until recently that the mathematical and physical foundations of QS have been developed in a series of publications. 5,[8][9][10]65,68,[148][149][181][182][183][184][185][186] In those articles, several new theoretical definitions, related to old concepts, were described. The first idea described was the so-called tagged set concept.…”
Section: Mathematical Aspects Of Quantum Similaritymentioning
confidence: 99%
“…As reviews on quantum similarity can be found elsewhere (see, for example, references [1][2][18][19][20][21][22]), only general definitions will be given at this point. Quantum similarity provides a quantitative measure of the resemblance between two quantum objects, A and B [4].…”
Section: Molecular Quantum Similaritymentioning
confidence: 99%
“…A quantum similarity measure in coordinate space (rQSM) involving these two objects, z AB can be constructed using their corresponding density functions. Both density functions can be multiplied and integrated over the respective electronic coordinates in a convenient domain, weighted by a positive definite operator [2,18]. That is, ( ) ρ r are the first-order molecular electron density functions of the two molecular structures being compared and ( ) 1 2 , Ω r r is a positive definite operator.…”
Section: Molecular Quantum Similaritymentioning
confidence: 99%
See 1 more Smart Citation